Resisting persecution : Jews and their petitions during the Holocaust - Pegelow, Thomas; Gruner, Wolf, 1960- (Studies in contemporary European history, 2020)
"Since antiquity, European Jewish diaspora communities have used formal appeals to secular and religious authorities to secure favors or protection. Such petitioning took on particular significance in modern dictatorships, often as the only tool left for voicing political opposition. During the Holocaust, tens of thousands of European Jews turned to individual and collective petitions in the face of state-sponsored violence. This volume offers the first extensive analysis of petitions authored by Jews in nations ruled by the Nazis and their allies. It demonstrates their underappreciated value as a historical source and reveals the many attempts of European Jews to resist intensifying persecution and actively struggle for survival." --